Utilizing the TPACK Framework to Analyze the Decision-Making Processes of Pre-Service Mathematics Teachers in Choosing GeoGebra Activities - AKKOÇ, HATİCE (My University, 2022)
This study aims to explore the decision-making processes of pre-service mathematics teachers (PMTs) as they select GeoGebra activities that are freely available online. The theoretical framework of the study embraces the Technological Pedagogical Content Knowledge (TPACK) framework (Koehler and Mishra, 2009). Participants were thirty-six PMTs who were senior students enrolled in a four-year teacher preparation program at a state university in Istanbul, Turkiye. Data consist of thirty-six reports each of which includes a learning objective specified by PMTs, online links to the three GeoGebra activities selected by the participants based on the learning objective, the affordances and limitations of these activities. Participants’ views about the affordances and limitations were analyzed based on the components of the TPACK framework such as TK, CK, PK, TCK, PCK, TPK, and TPACK. The findings indicated that the participants' explanations about the affordances and limitations of the activities were mostly related to the technical (TK or TCK) and pedagogical aspects (especially PCK) rather than the technological pedagogical aspects (TPK or TPCK). The paper will discuss the findings concerning how to develop the knowledge required for successful technology integration in teacher preparation.